2021
DOI: 10.1093/ofid/ofab330
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Care Outcomes Among People With HIV in the United States

Abstract: Background Fewer than 70% of people living with HIV (PLHIV) in the United States have achieved durable viral suppression. To end the HIV epidemic in the United States, clinicians, researchers, and public health practitioners must devise ways to remove barriers to effective HIV treatment. To identify PLHIV who experience challenges to accessing healthcare, we created a simple assessment of social determinants of health (SDOH) among PLHIV and examined the impact of cumulative social and economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Of 8,022 PLWH, 4943 (61.6%; 95%CI 60.5-62.7%) received at least one COVID-19 vaccine dose and 4538 (56.6%; 95%CI 55. 5 The percentage of PLWH who received at least one COVID-19 vaccine dose ranged from 30.9% among those without a CD4 count and viral load measurement in 2020 to 78.1% among those who received an influenza vaccine in 2019-2020. Compared to PLWH 18-29 years old, vaccination was more likely among PLWH aged 50 years old and older.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 8,022 PLWH, 4943 (61.6%; 95%CI 60.5-62.7%) received at least one COVID-19 vaccine dose and 4538 (56.6%; 95%CI 55. 5 The percentage of PLWH who received at least one COVID-19 vaccine dose ranged from 30.9% among those without a CD4 count and viral load measurement in 2020 to 78.1% among those who received an influenza vaccine in 2019-2020. Compared to PLWH 18-29 years old, vaccination was more likely among PLWH aged 50 years old and older.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PLWH with lower CD4 counts may mount an inadequate response to vaccination and may require increased support to complete a newly recommended three-dose vaccination series for people with untreated or advanced HIV. Social determinants of health affecting uptake of COVID-19 vaccination likely overlap with those affecting clinic attendance, antiretroviral adherence, and viral suppression [5]. In contrast, ADAP enrollment was associated with greater vaccine uptake; case workers facilitate access to vaccination through assistance with finding vaccination sites, appointment scheduling, and transportation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These needs, or social determinants of health (SDOH), encapsulate a wide range of economic, social, and environmental factors 31,32 . In a study of 15,964 PWH in the United States, 23% reported at least one SDOH indicator, while 25% indicated 4 or more indicators 30 . Further, 31.7% had di culties with transportation, which is consistent with the 32.5% of our cohort who received transportation coordination from a CHW 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 15,964 PWH in the United States, 23% reported at least one SDOH indicator, while 25% indicated 4 or more indicators 30 . Further, 31.7% had di culties with transportation, which is consistent with the 32.5% of our cohort who received transportation coordination from a CHW 30 . Our data demonstrate that emotional support was the most commonly reported purpose of CHW encounter.…”
Section: Discussionmentioning
confidence: 99%